Sexual size dimorphism and sex ratio in arthropod ectoparasites: contrasting patterns at different hierarchical scales. Issue 12 (October 2018) - Surkova, Elena N.; Korallo-Vinarskaya, Natalia P.; Vinarski, Maxim V.; Stanko, Michal; Warburton, Elizabeth M.; van der Mescht, Luther; Khokhlova, Irina S.; Krasnov, Boris R.
Graphical abstract: Highlights: Sexual size dimorphism in fleas, but not in gamasid mites, conforms to Rensch's rule. The relationships between sexual size dimorphism and sex ratio are strongly pronounced at the infrapopulation scale. These relationships are weak at the suprapopulation scale, and absent at the xenopopulation scale. The pattern of the relationship between sexual size dimorphism and proportion of males in populations is scale-dependent. This pattern is positive at the lowest scale and tends to be negative at the highest scale. Abstract: The aims of this study were to determine whether sexual size dimorphism in fleas and gamasid mites (i) conforms to Rensch's rule (allometry of sexual size dimorphism) and (ii) covaries with sex ratio in infrapopulations (conspecific parasites harboured by an individual host), xenopopulations (conspecific parasites harboured by a population of a given host species in a locality) and suprapopulations (conspecific parasites harboured by an entire host community in a locality). Rensch's rule in sexual size dimorphism was tested across 150 flea and 55 mite species, whereas covariation between sexual size dimorphism and sex ratio was studied using data on ectoparasites collected from small mammalian hosts in Slovakia and western Siberia. For fleas, we controlled for the confounding effect of phylogeny. The slope of the linear regression of female size on male size was significantly smaller than 1 in fleas, but did not differ from 1 in mites. The proportion of males in flea infrapopulations significantly increased with an increase in the female-to-male body size ratio. The same was true for obligatory haematophagous mites. No relationship between sex ratio and sexual size dimorphism was found for xenopopulations of either taxon or for mite suprapopulations. However, when controlling for the confounding effect of phylogeny, a significant negative correlation between sex ratio and sexual size dimorphism was revealed for flea suprapopulations. We conclude that (i) some macroecological patterns differ between ectoparasite taxa exploiting the same hosts (allometry in sexual size dimorphism), whereas other patterns are similar (sexual size dimorphism-sex ratio relationship in infrapopulations), and (ii) some patterns are scale-dependent and may demonstrate the opposite trends in parasite populations at different hierarchical levels.